Avaliação da resistência de união em reparos entre resinas compostas bulk fill, bulk fill flow e nanoparticulada envelhecidas - Donini, Emerson Delazari (2017)
Repairing on composite resin restorations can be a conservative alternative to remedy restoration failures as it preserves parts of the tooth that would normally be removed during a complete exchange. The objective of this work was to evaluate the bond strength of post-repair and aging composite resins in different solutions (distilled water, 75% water-alcohol and 0.02N nitric acid). Five composite resins were used, being a conventional resin (Z350) and four bulk fill Filtek Bulk fill (FBF), Filtek Bulk Fill Flow (FBFF), Surefill SDR Flow (SURE) and Opus Bulk Fill Flow (OPUS). Specimens 2x2x5 mm were prepared in prefabricated silicone molds and aged for 30 days, after which the resins were treated with a surface treatment and soon after the repair, becoming a CP with 2x2x10mm. The repairs were performed in the same silicone mold by combining all the resins in the sample, forming 75 groups (n = 10), and immersed again for 30 days in the evaluated solutions. After, the CPs were submitted to the tensile test with the machine DL-200 MF - Emic DL line. The mean values obtained for each CP were submitted to the Kruskall-Wallis test, followed by Dunn's post-test (p <0.05). According to the experimental methodology for Z350 aged in distilled water, the repairs made with the Z350 itself (5.82 + 2.10) and the FBFF (5.88+3.06) showed no statistical differences. For the repairs between FBF (7.44 + 1.68) and OPUS (7.25 + 2.85) there were no statistically significant differences, however, they were higher than SURE (3.59 + 1.57). In 75% water/alcohol solution, all repairs made on the Z350 base were statistically similar. For the 0.02N nitric acid solution and for the Z350 base, the repairs with FBFF (4.37+1.08) and SURE (4.44+1.29) showed no differences between themselves and with FBF (3,37+0.54) and OPUS (5.43+1.21), but were higher than those with Z350 (2.27 + 0.61). When the base was FBF and the solution to distilled water, repairs with FBF (4.90 + 1.98), FBFF (5.50 + 1.56) and SURE (6.08 + 2.01) did not show Differences. Repairs with OPUS were higher (7.32 + 1.74) compared to Z350 (3.82 + 1.85). FBF as a base in the 75% water / alcohol solution and 0.02N nitric acid the repairs showed no differences between them. For the FBFF base in the distilled water, the repair with the same FBFF (7.64 + 2.86) showed no differences with the other resins. (3,63 + 2,86), SURE (7,25 + 3,03), and OPUS (6,83 + 2,40) compared to the bulk fill flow resins, FBFF (7,64 + 2,86). Which did not show significant differences between them. For the 75% water / alcohol solution there were no significant differences between the repairs compared to each other. For the 0.02N nitric acid solution, there were no statistically significant differences when comparing the Z350, FBFF and OPUS resins with each other. The results were higher for SURE (9.93+3.91) when compared to FBF (5.67+1.83) both as repair. For the SURE base in the distilled water solution, there were no significant differences between all the repairs. In the 75% water / alcohol solution, for repairs with Z350 (1.55+067), FBF (2.24+1.09), SURE (2.37+0.85) and OPUS (2.13+0.75) were not different from each other, but were better than the FBFF (2.76+0.73), and the FBF (2.24+1.09) was not different when compared to the others. In the 0.02N nitric acid solution, all repairs were statistically similar to each other. For OPUS as a base, in the distilled water solution, repairs with SURE (3.20+0.67) and OPUS (4.09+1.12) were similar to each other. The Z350 (2.83+1.36) and FBF (2.73+0.94) showed no significant differences among themselves, but compared to the FBFF resin (5.04+1.27) had worse results than this. In 75% water/ethanol solution and nitric acid there were no statistically significant differences between the resins used in the repair. According to the results obtained, it was possible to verify that, in the majority of the comparisons made among the composite resins evaluated in this study, the nanoparticulate resin presented the worst values of bond strength when used as repair. On the other hand, the bulk fill composites presented the best behavior when used as repair.